IMPACT OF TECHNOLOGY IN FINANCIAL SERVICES: A STUDY AMONG THE RETAIL CUSTOMERS OF FINANCIAL SERVICES IN CHENNAI CITY - 1 A. HariKrishnan, 2 Dr. G. Rajesh Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The present study is carried out to investigate the effectiveness of technology in financial services among retail customers in Chennai city. The purpose of the study is to assess the current level of technology adoption, identify factors influencing customer satisfaction, and evaluate the impact of demographic variables on the usage of financial technology. Survey method is adopted for data collection from 300 retail customers. The collected data are for analyzed by using Chi-square test, ANOVA, correlation, and multiple regression analyses. The findings disclose strong association between education level and technology usage, differences in satisfaction levels across income groups, and a moderate positive correlation between technology usage and customer satisfaction. The study offers with recommendations for enhancing the effectiveness of technology in financial services through improved user training, user-friendly interfaces, and secure systems.